2020
DOI: 10.3389/fpsyg.2020.02012
|View full text |Cite
|
Sign up to set email alerts
|

The Hummingbird Project: A Positive Psychology Intervention for Secondary School Students

Abstract: Mental health in schools has attracted a lot of attention in recent years. Positive Psychology Interventions (PPIs) in secondary schools have been shown to improve mental health outcomes for students. Previous PPIs have tended to be delivered by trained Psychology specialists or have tended to focus on a single aspect of Positive Psychology such as Mindfulness. The current study involved 2 phases. Phase 1 was a pilot PPI, delivered by current university students in Psychology, which educated secondary school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 64 publications
4
21
0
Order By: Relevance
“…Indirectly, it can also reduce the long-term symptoms of mental disorders [ 43 ]. A recent study of positive interventions in schools [ 44 ] has shown that these interventions are universally beneficial. They are particularly helpful among the adolescents described by their teachers as most in need of mental health care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirectly, it can also reduce the long-term symptoms of mental disorders [ 43 ]. A recent study of positive interventions in schools [ 44 ] has shown that these interventions are universally beneficial. They are particularly helpful among the adolescents described by their teachers as most in need of mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions also reduce the sense of loneliness of students with mental health problems. Such students often feel alienated and stigmatized, prefer not to ask for help, and remain silent, not to be labeled as problematic [ 44 ]. In agreement with the previous reports [ 35 ], our study shows the importance of including positive mental health scales in school-based mental health assessment programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite, this growing concern, Positive Psychology has been extensively a target of research which has led, so far, to interesting results. From the benefits of positive psychology interventions in improving wellbeing and diminishing depression, anxiety or stress (Boiler et al, 2013 ; Carr et al, 2020 ), to contributing to employees' performance and productivity (Kour et al, 2019 ), to reducing distress in people diagnosed with clinical disorders (Chakhsii et al, 2018 ), or even promoting resilience and hope through specific interventions in schools settings (Platt et al, 2020 ). Positive psychology practices have constructive impacts on people's everyday lives such as reducing stress and anxiety, increasing resilience and promoting self-growth, wellbeing, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Sample 1 was 1087 students from a university in the North West of England[25] Sample 2 was 933 adolescents from the North West of England[26]. Sample 3 was 331 students from a university in the North West of England[25].…”
mentioning
confidence: 99%